MSGF : a checkered saga? - Agarwalla, Sobhesh Kumar; Barua, S. K. (Samir K.) (London : SAGE Publications Ltd, 2017)
The liberalization of the Indian economy that began in earnest in the middle of 1991 was baptized by the securities scam of 1992. The scam sent the Indian capital markets into a tail spin and created a major road block to the process of unshackling the Indian economy. Despite the naysayers however, the government went ahead with the opening up of the financial sector and permitted Foreign Institutional Investors (FIIs) to invest in the Indian capital markets. FIIs were also permitted to set up business in India and offer their services to Indian customers. By late 1993, Morgan Stanley had decided to enter India. It set up the Morgan Stanley Asset Management Company and launched its maiden mutual fund scheme, the Morgan Stanley Growth Fund (MSGF), inviting Indian investors to subscribe to the units of the fund. Investors were over-awed by the opportunity to benefit from the expertise of an internationally renowned firm with assets of over US $ 90 billion under management spread across the world.
Originally published: Agarwalla, S. K., & Barua, S. (2014). MSGF a checkered legacy?. F&A0515. Ahmedabad: Indian Institute of Management, Ahmedabad.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Morgan Stanley (Firm); Morgan Stanley Asset Management Company; Deregulation -- India; Financial services industry; India -- Economic policy; India -- Economic conditions